Penerapan Kebijakan Pengarusutamaan Gender dalam Program Pendidikan - Vivi Rahim Hentihu; M Chairul Basrun Umanailo; Saidna Zulfiqar Bin Tahir; A Yusdianti Tenriawali; Darwin Abd Radjak (Mahesa Research Center, 2021)
This article was written with the aim of the implementation of gender mainstreaming is an important government program, this study aims to examine how the implementation of gender mainstreaming policies (PUG) in education programs. The problem is focused on the implementation of gender mainstreaming policies in education programs by the Education and Culture Office of Buru Regency because the initial data encountered in the implementation of gender mainstreaming is still limited to socialization and discourse but has not progressed to policy implementation. This research is a qualitative research, the source of data is obtained from purposively selected informants such as the Head of Service, Head of Division at the Education and Culture Office of Buru Regency, and the Head of SMP 9 Buru, and SMK 7 Buru who are considered to have knowledge that is in accordance with the research objectives. Data collection techniques using interviews and documentation. Analysis of the data using the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The data validity technique was carried out by source triangulation and technical triangulation. This study concludes that the District Education Office of Buru has not yet made or initiated legal regulations that support gender mainstreaming. On the other hand, the education office, which should be an institution that carries out mandatory affairs in the field of education, has not fully implemented or implemented gender-based policies so that it will affect directly related institutions or institutions such as schools and other supporting institutions in the education sector.